Cross her heart - Leigh, Melinda (Seattle : Montlake, 2020)
"When her sister Erin is murdered and Erin's husband goes missing, Philadelphia homicide detective Bree Taggert vows to uncover the secrets of her sister's life and death but when the danger hits close to home, her own family is caught in a death grip." --
108490
Keywords: Sisters -- Death -- Fiction; Murder -- Investigation -- Pennsylvania -- Philadelphia; Missing persons -- Investigation; Women detectives; Police -- Pennsylvania -- Philadelphia; Detective and mystery stories, American; Detective and mystery fiction; Thrillers (Fiction); Suspense fiction